Tamoxifen in Duchenne muscular dystrophy (TAMDMD): study protocol for a multicenter, randomized, placebo-controlled, double-blind phase 3 trial - Nagy, Sara (Trials, 2019)
BACKGROUND: Duchenne muscular dystrophy (DMD) is an inherited neuromuscular disorder of childhood with a devastating disease course. Several targeted gene therapies and molecular approaches have been or are currently being tested in clinical trials; however, a causative therapy is still not available and best supportive care is limited to oral glucocorticoids with numerous long-term side effects. Tamoxifen is a selective estrogen receptor regulator, and shows antioxidant actions and regulatory roles in the calcium homeostasis besides its antitumor activity. In a mouse model of DMD, oral tamoxifen significantly improved muscle strength and reduced muscle fatigue. This multicenter, randomized, double-blind, placebo-controlled phase III trial aims to demonstrate safety and efficacy of tamoxifen over placebo in pediatric patients with DMD. After completion of the double-blind phase, an open-label extension of the study will be offered to all participants. METHODS/DESIGN: At least 71 ambulant and up to 20 nonambulant patients with DMD are planned to be enrolled at multiple European sites. Patients will be randomly assigned to receive either tamoxifen 20 mg or placebo daily over 48 weeks. In the open-label extension phase, all patients will be offered tamoxifen for a further 48 weeks. The primary endpoint of the double-blind phase is defined as the change of the D1 domain of the motor function measure in ambulant patients or a change of the D2 domain in nonambulant patients under tamoxifen compared to placebo. Secondary outcome measures include change in timed function tests, quantitative muscle testing, and quantitative magnetic resonance imaging of thigh muscles. Laboratory analyses including biomarkers of tamoxifen metabolism and muscle dystrophy will also be assessed. DISCUSSION: The aim of the study is to investigate whether tamoxifen can reduce disease progression in ambulant and nonambulant patients with DMD over 48 weeks. Motor function measures comprise the primary endpoint, whereas further clinical and radiological assessments and laboratory biomarkers are performed to provide more data on safety and efficacy. An adjacent open-label extension phase is planned to test if earlier initiation of the treatment with tamoxifen (verum arm of double-blind phase) compared to a delayed start can reduce disease progression more efficiently. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03354039. Registered on 27 November 2017.